Dream destinations : 100 of the world's best vacations. (New York : Life Books, 2008)
Presents one hundred travel destinations around the globe, from an African safari or an exploration of Australia's Great Barrier Reef to a beach on Martha's Vineyard, accompanied by special recommendations on places to visit while traveling.
At head of title on cover: Life.
Keywords: Travel -- Guidebooks